PENCATATAN DAN PENGAKUAN SUMBERDAYA MANUSIA DALAM AKUNTANSI - Warno, Warno (JURNAL STIE SEMARANG, 2011)
In the literal sense, "human resource accounting" means accounting for people as an organizational resource. This involves measuring the costs incurred by business corporations and other organizations to recruit, select, hire, train and develop human assets. There are three functions of human resource accounting, namely (1) as a framework to assist decision making in human resources, (2) To provide quantitative information about the costs  and  value  of  human  resources  as  an  element  of  the  organization,  and  (3)  motivate managers to adopt HR information in making decisions concerning people. Several methods can be used to determine the value of human resources: - Capitalization of Salary or Wages - Costs of acquisition - Expenses beginning - Cost of replacement - Methods of economic value